ByzRev 06.2024.039: Gregory Tucker, The Hymnography of the Middle Byzantine Ecclesiastic Rite & its Festal Theology.: Introduction – Edition & Translation – Commentary (Studies in Eastern Christian Liturgies 5). Münster: Aschendorff 2022. - Afentoulidou, Eirini (The Byzantine Review, 2024)
Gregory Tucker, The Hymnography of the Middle Byzantine Ecclesiastic Rite & its Festal Theology. Introduction – Edition & Translation – Commentary (Studies in Eastern Christian Liturgies 5). Münster: Aschendorff 2022. XXVI, 661 pp. – ISBN 978-3-402-21772-6 (€ 68.00)